2009
DOI: 10.1016/j.chemosphere.2008.11.073
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition and mineralization of aquatic humic substances (AHS) in treating landfill leachate using the Anammox process

Abstract: a b s t r a c tAquatic humic substance (AHS) in landfill leachate is resistant to biodegradation, especially in anaerobic habitats. However, we reported here for the first time that AHS was completely biodegraded with the anaerobic ammonium oxidation (Anammox) process. As a result of aromatic-ring cleavage and mineralization, carboxylic and aliphatic organics were significantly produced, the contents of chromophores such as quinoid and ketone were remarkably decreased to decolorize the leachate, and produced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 27 publications
0
14
0
2
Order By: Relevance
“…However, there are reports on other heterotrophic bacterial strains, except for SRB, reducing SO 4 2-as the terminal electron acceptor while utilizing organic substrates in a similar manner as SRB under anaerobic conditions (Liang et al 2009). Four facultative anaerobic species, Bacillus sp., Paenibacillus sp., Bacteroides sp.…”
Section: More Nhmentioning
confidence: 97%
See 1 more Smart Citation
“…However, there are reports on other heterotrophic bacterial strains, except for SRB, reducing SO 4 2-as the terminal electron acceptor while utilizing organic substrates in a similar manner as SRB under anaerobic conditions (Liang et al 2009). Four facultative anaerobic species, Bacillus sp., Paenibacillus sp., Bacteroides sp.…”
Section: More Nhmentioning
confidence: 97%
“…The ''conventional'' anammox, however, is not sustainable in a medium where a high concentration of easily biodegradable organic matter is present (Chamchoi et al 2008) as denitrifying bacteria outcompete the anammox organisms. Anammox process has still been successfully applied for treatment of landfill leachate (Liang et al 2009) containing organic matter of more refractory nature.…”
Section: More Nhmentioning
confidence: 99%
“…Numerous methods have been used to reduce the HA in drinking water, such as membrane separation, ultra-filtration, chemical coagulation, ion exchange, adsorption, biodegradation, and so on (5)(6)(7)(8)(9)(10). Among these methods, adsorption method appears to be one of the most promising alternatives because of its simplicity of design, low-cost, and ease of operation.…”
Section: Introductionmentioning
confidence: 98%
“…The consistency of the inhibition model to the experimental data was fitted with minimum squared errors method and it was found that modified non-competitive is the most representative model. Also, some researchers used the modified non-competitive model to express the heavy metal inhibition on the biochemical process [27,34,36,37]. Therefore, IC50 values for short-term inhibition was determined by modified non-competitive inhibition model.…”
Section: Short-term Effect Of Cu On Anammoxmentioning
confidence: 99%